Knowledge and Practices in Viral Hepatitis Management and its Challenges: A Survey Among Ayurveda Physicians of Kerala - Akhila R Kurup,; Indulekha, (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda physicians provide treatment for viral hepatitis patients in Kerala. A survey was conducted to assess the knowledge and practices in viral hepatitis management among Ayurveda physicians (APs) of Kerala.Materials & Methods: An in depth telephonic interview and a questionnaire were administered among APs in Kerala for assessing knowledge about viral hepatitis and its treatment.Results: All the 150 participants were aware about different types of viral hepatitis. Around 90% Aps know about complications of viral hepatitis and mode of transmission.  Only 20% screen their patients before performing Panchakarma therapy and para-surgical procedures in their clinic. All physicians depends liver function test for diagnosing and assessing different types of Hepatitis; only  6.6% physicians additionally prescribe Ultrasonogram of abdomen and viral load. Majority physicians reported chronicity for HBV and HCV infections and good outcome/ curable for hepatitis A. Only a few physicians were documenting the cases in their clinics. The lack of structured case proforma for documentation and guidelines for management, research, patient education and time constraints was reported as challenges in the treatment of viral hepatitis by the majority of AP in the current survey. Conclusion: The majority of doctors had a good knowledge of the different types of viral hepatitis and they depended on laboratory examinations for diagnosis and evaluation. The treatment strategies were based on the treatment principles of Kamala and Panduroga in Ayurveda.